The transexual in “El lugar sin límites”: Monstruosity, normas and punishment - Martínez Díaz, María (2026)
This article presents an interpretation of the novel by José Donoso El Lugar sin límites (1966). It is a literary analysis focused on the character called La Manuela, he aims to reflect on the emergence of the transsexual in the male order dominated by violence and the mechanisms of power. At the same time the analysis will revolve around the character`s body from wich it will be possible to notice the construction processes of gender identity and the normative violence exerted on the body following the heteronormative principles.